Entrepreneurship Training on Soft Thorn Milkfish Processing at the INS Producer Cooperative Assisted Group in Teluk Laikang, Takalar Regency - Idayanti Nursyamsi; Muhammad Idrus Taba; Cepi Pahlevi; Nursinah Amir; Andi Nur Baumassepe Mappanyompa; Andi Reni; Wadzibah Nas; Andi Muhammad Farid Hadi; Andi Muhammad Fakhrul Wahyudi (Cita konsultindo, 2024)
INS Producer Cooperative is a business partner engaged in the fisheries and marine sector. Specifically, partners aim to improve people's living standards in the blue economy sector. Apart from that, the cooperative program is supported by coastal fishing communities as part of the community empowerment program. The cooperative-assisted fishing community still does not have adequate knowledge in processing innovative milkfish technology. There is also still insufficient knowledge of developing an entrepreneurial spirit to achieve family prosperity. This Community Service offers solutions in the form of entrepreneurship training activities and assistance in processing soft spiny milkfish as a solution to the problems faced by coastal fishing communities in overcoming the problem of poverty alleviation, which has an impact on improving community welfare. The aim of this PKM is that fishing communities are capable of entrepreneurship and can master the technology for processing soft spiny milkfish products to create family business opportunities and achieve family economic prosperity for coastal fishing communities assisted by the Cooperative.